2022
DOI: 10.3897/phytokeys.204.85746
|View full text |Cite
|
Sign up to set email alerts
|

Hymenasplenium tholiformis (Aspleniaceae), a new fern species from southeastern Xizang, China based on morphological and molecular evidence

Abstract: A new species of Aspleniaceae, Hymenasplenium tholiformis sp. nov., is described from Medog County in southeastern Xizang, China. The new species is morphologically similar to H. apogamum and H. szechuanense, but the former has ascending pinnae, pinna apex obtuse to rounded, pinna-marginal teeth entire, and veins terminating just below marginal teeth. Phylogenetic analysis based on five plastid markers confirmed that this new species represents a diverging lineage in the H. excisum subclade of Hymenasplenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This lineage formed a separate clade with H. tholiformis, but lacked support. Another lineage (BS = 92%, BS = 96%, BI p = 1) was comprised of accessions of the new taxon in this study including collections identified as a proposed new species (sp8, Zhang Liang 4781) and H. obscurum (Wu et al WS2552;Wu et al WS2176) in former studies (Xu et al 2018a;Qiu et al 2022). There was one more lineage (BS = 88%, BS = 92%, BI p = 1) that was comprised of several divergent lineages, but included accessions all identified as H. excisum.…”
Section: Chloroplast Dna Phylogenymentioning
confidence: 92%
See 1 more Smart Citation
“…This lineage formed a separate clade with H. tholiformis, but lacked support. Another lineage (BS = 92%, BS = 96%, BI p = 1) was comprised of accessions of the new taxon in this study including collections identified as a proposed new species (sp8, Zhang Liang 4781) and H. obscurum (Wu et al WS2552;Wu et al WS2176) in former studies (Xu et al 2018a;Qiu et al 2022). There was one more lineage (BS = 88%, BS = 92%, BI p = 1) that was comprised of several divergent lineages, but included accessions all identified as H. excisum.…”
Section: Chloroplast Dna Phylogenymentioning
confidence: 92%
“…Ju & K.W. Xu ( Lin and Viane 2013 ; Xu et al 2018a ; Qiu et al 2022 ). Xu et al (2018a) estimated that at least six undescribed species exist in this subclade and numbered four of them from sp8 to sp11, but without taxonomic description and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ju & K.W. Xu, and Selliguea wusugongii Liang Zhang, X.P.Fan & Li Bing Zhang have been discovered ( Fan et al 2021 ; Qiu et al 2022a , b ). When we studied the lycophytes from these collections, we found some materials of Selaginella belonging to the S. vaginata group, but differing from all recognized species in this group.…”
Section: Introductionmentioning
confidence: 99%